Eksplorasi Kedisiplinan Kerja Pegawai melalui Perspektif Organisasional di PT PLN (Persero) ULP Kediri Kota - Azizah N. Amalia; Nilawati Fiernaningsih (Faculty of Social and Political Science, 2025)
Work discipline has an important role in supporting employee performance and the efficiency of company operations. This study aims to analyse the level of work discipline of employees at PT PLN (Persero) ULP Kediri Kota and identify the factors that influence it. The approach used is descriptive qualitative with data collection methods in the form of observation, interviews, and documentation. The results showed that in general employee discipline was in the good category. This is reflected in compliance with working hours, the application of dress ethics, and the implementation of tasks according to their respective responsibilities. However, there are still some obstacles in the implementation of work discipline, including late attendance and employees' lack of understanding of the company's internal procedures. Factors that influence the level of work discipline include a comfortable and supportive work environment, internalisation of corporate culture values such as AKHLAK (Amanah, Kompeten, Harmonious, Loyal, Adaptive, and Collaborative), and the effectiveness of communication within the organisation. These three factors play an important role in shaping disciplined and responsible work behaviour. The findings are expected to be taken into consideration for management in improving the supervision and coaching system.